THE INFLUENCE OF FAMILY ENVIRONMENT ON CHILDREN'S ACADEMIC ACHIEVEMENT - Mudzakir Mudzakir; Cynthia Petra Haumahu; Sunanto Sunanto; Al-Amin (INJOSEDU: International Journal of Social and Education, 2025)
This study aims to analyze the relationship between family environment and children's academic achievement through literature analysis method. The results showed that there is a significant relationship between a supportive family environment and children's academic achievement. Emotional support, characterized by recognition of children's efforts, confidence building, and providing a safe space for learning, plays an important role in children's academic motivation. In addition, parents' active involvement in education - including checking homework, attending school meetings and providing learning resources at home - plays a role in improving academic achievement. A conducive learning environment at home, filled with reading materials, clear expectations about education and structured study habits, also supports children's cognitive development and academic achievement.